Adherence to a regulation that aims to prevent and treat malnutrition—The case of Swedish elderly care. Issue 7 (July 2019) - Skinnars Josefsson, Malin; Nydahl, Margaretha; Persson, Inger; Mattsson Sydner, Ylva
Highlights: Adherence to new regulation not associated to increased nutritional status among elderly. New regulation calls for preventive routines, but actions are unchanged in practice. Some actions dominate regardless of updated preventive routines or screening results. Abstract: Malnutrition constitutes a serious and challenging problem in elderly care. In 2015, a Swedish regulation that aims to prevent and treat malnutrition came into effect. This study set out to explore associations between level of adoption of the regulation reported as: no, started, yes, in a previous survey, and registrations in a national quality registry. Registry data on screening and actions extracted from the first trimester in 2014 (n=18967), 2016 (n=20318) and 2017 (n= 25669) represented 209, 197 and 199 of 290 Swedish municipalities respectively. A repeated measures ANOVA showed that there was no effect on screened nutritional status, Pearson's chi-square that there were minor differences in types of actions, and regression analysis that the number of actions increased on average by 0.3 due to a higher level of adoption of the regulation. Over the years studied, five actions were prominent regardless of level of adoption or screened nutritional status. Hence, to date, no firm conclusions regarding effects of the regulation can be drawn. Despite the regulatory nature, it appear as if the regulation and the level of adoption reported so far is routine in theory, although not yet leveraged to an implemented practice visible in the quality registry but instead decoupled from practice.